PRAKTIK WUDHU SISWA DALAM TINJAUAN FIQIH - Raihan (CV. Adiba Aisha Amira, 2026)
Ablution (wudu) is one of the requirements for performing prayer, and holds a crucial place in Islamic teachings. It is not only understood as cleansing the body but also as a form of obedience to the commands of Allah SWT. In practice, students are still found to have failed to perform ablution according to Islamic jurisprudence (fiqh), including in terms of sequence, completeness of ablution, and understanding of the pillars and sunnah of ablution. This problem indicates a discrepancy between the theory learned in fiqh lessons and the actual practice students engage in in their daily lives. This study aims to determine students' ablution practices, analyze their compliance based on observations of fiqh, and identify factors that contribute to errors in performing ablution. This study used a qualitative descriptive method, collecting data through direct observation and literature review of various fiqh journals and books. The results indicate that some students still make errors such as irregularity in the order of ablution, uneven distribution of air to certain body parts, and a lack of understanding of the pillars and sunnah. Furthermore, fiqh instruction, which focuses too much on theory without practice, is a major contributing factor to students' poor ablution skills. Therefore, more practical learning methods, through drilling and hands-on practice, are needed to enable students to understand and perform ablution correctly in accordance with Islamic law.